How sleep quality is associated with blood glucose levels in elderly diabetics melitus: A critical study at Cukir Community Health Center - Santoso, Syaputra Dwi; Firdaussy, Alifa Putri Syaharany Amalliya; Muhammad, Ikhlas Nur (Indonesian Red Crescent Humanitarian Journal, 2025)
This research aims to analyze the relationship between sleep quality and blood glucose levels in elderly patients with diabetes mellitus at Puskesmas Cukir, Jombang. Diabetes mellitus (DM) is a common chronic disease among the elderly, and poor sleep quality has been identified as a factor that may worsen diabetes management. This study is important as it addresses the gap in understanding how sleep quality directly impacts diabetes control, particularly in elderly individuals, where both sleep disturbances and diabetes are prevalent. Previous research has typically studied sleep quality or diabetes management separately, with few examining their interrelationship in elderly diabetic patients. The study used a quantitative approach with a cross-sectional design, involving 80 diabetic patients aged 50-60 years. Data was collected using the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, while blood glucose levels were measured concurrently. The results revealed that 68% of respondents had poor sleep quality, and 49% had uncontrolled blood glucose levels. Statistical analysis using Spearman’s correlation test showed a significant relationship between sleep quality and blood glucose levels (r = 0.823, p = 0.016), indicating that poor sleep quality is linked to higher blood glucose levels. This study concludes that poor sleep quality negatively affects blood glucose control in elderly patients with diabetes. The findings suggest that improving sleep quality could be an essential intervention for better glucose control and preventing diabetes-related complications. Healthcare professionals should consider sleep quality in diabetes management and provide interventions to improve sleep hygiene in elderly diabetic patients.